Factors influencing the collaboration between Federal and Local Governments in Malaysia - Vellasamy, Sithra Devi (2019)
Effective collaboration between public agencies is necessary for the delivery of goods and services to the people; and expanding knowledge in this area will benefit the society. Hence, this study sought to identify the factors that influence and improve the collaboration outcomes between the Federal and Local Government in Malaysia by empirically testing the Ansell & Gash Contingency Model of Collaborative Governance. Three broad based theories, namely Transformational Leadership, Resource Dependency and Theory of Collaborative Advantage were used to underpin the conceptual framework which had eight constructs namely Transformational Leadership (idealized influence, individualized consideration, intellectual stimulation, inspirational motivation), Resource Dependency (funding, skills and expertise, geographical coverage), Collaborative Governance (planning, monitoring and feedback), Relational Capital (trust, commitment, communication) and Interdependence (task, goal, reward). This was a quantitative study conducted among Malaysian Federal Government and Local Government officers, in particular, the Ministry of Urban Well Being, Housing and Local Council. The data were analyzed using both SPSS and Smart PLS 3.0. The findings revealed that Transformational Leadership and Resource Dependency both had positive relations with Relational Capital and Interdependence; and all these constructs had positive influence towards improving the Star Rating and Inter-Organizational Learning of local councils. Contrary to the study prediction, Collaborative Governance did not moderate the relationships between the constructs. Instead, a post-hoc analysis found that Collaborative Monitoring and Feedback mediated the relationships of the independent (Relational Capital and Interdependence) and dependent (Collaboration Outcome) variables. The findings from this study provide new insights for managers and leaders on aspects that could improve the collaboration processes between the Federal and Local Government in Malaysia.